MANAJEMEN PENDIDIKAN DI PONDOK PESANTREN BAIT ET-TAUHIED - Adawiah, Diah Robiatul; Zohriah, Anis (Idaarah: Jurnal Manajemen Pendidikan, 2024)
The purpose of this study is to determine the management of education in the Islamic boarding school Bait Et-Tauhied. The research method used is field research with a qualitative approach. Data collection is done by observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and verification (drawing conclusions). The results showed; forms of education management in Pondok Pesantren Bait Et-Tauhied include; Management Planning through the preparation of character education programs through the vision, mission and objectives of education in Islamic boarding schools, Organizing Management through the distribution of job descriptions in each field implemented, Actuating Management by, organizing and directing the person in charge of activities and the implementers of activities to immediately realize the planned program, Management Controling includes controlling and supervising and ensuring activities run well.